Congenital aplasia of left kidney in a brown layer chicken - Alper Sevimli; Deniz Mısırlıoğiu (Eurasian Journal of Veterinary Sciences)
This paper reports a case of aplasia of left kidney encountered in a fifteen-week old Brown layer (Isa Brown) chicken in a commercial farm in Bursa region. At necropsy it was seen that the left kidney was absent and that a abnormally shaped and dilated corresponding ureter was present. There was mild hyperthrophy ot the right kidney. In additon, evidence of fibrinous pericarditis, perihepatitis and amyloidosis in the liver and spleen was seen at macroscopical and microscopical examination.